Delay-dependent H∞ control for LPV systems with time delays. (6th November 2008) - Sun, Man; Jia, Yingmin; Du, Junping; Yuan, Shiying
In this paper, the delay-dependent H∞ control problem is considered for Linear Parameter-Varying (LPV) systems with time-varying delays. By using a descriptor model transformation of the system and by applying Park's inequality for bounding cross terms, some sufficient conditions on H∞ performance analysis are given in terms of Linear Matrix Inequalities (LMIs). Based on these conditions the state-feedback controller is designed. A numerical example is included to illustrate the proposed method.